The Great Powers’ Policy towards the Central-Eastern Europe in the Time of the Paris Peace Conference (1919) – the Nature of the Game and the Motives of the Players - Żurawski vel Grajewski, Przemysław (Дриновський збірник, 2020)
The Paris Peace Conference was convoked to end the World War I and to construct the new post-war Versailles order in Europe that was being shaped in the years 1918-1923. The Great Powers’ leaders who gathered in Paris as well as the delegates of the smaller states who were doing their best to win the support of the former both were playing the political game motivated with the interests of their respective countries. Those interests sometimes crumpled into surprisingly complicated nodes. A number of them concerned the Central-Eastern European issues. That was the region where the scale of complexity was the largest one.